Conversion of International Accounting Standards: Taking Indian Accounting Standards into Consideration - TULSYAN, PRATEEK (2010)
ABSTRACT This dissertation is the study of conversion the accounting standards to a global accounting standards i.e. International Financial Regulatory Services. However, the main focus of the study is on the conversion of Indian Accounting Standards to International Accounting Standards. The study also shows the focus on the reactions of the people of India and their knowledge on the International Accounting Standards. It is also gives a knowledge to all the people who is not familiar with IFRS. The research methodology that has been done for this study is the interview questions which has been carried out in India carried out in 10 firms including accounting firms, banks and stock brokerage firms.